Desenvolvimento e Centralidade da Indústria: Uma Atualização do Debate no Brasil - João Batista Pamplona (Universidade Regional do Noroeste do Estado do Rio Grande do Sul, 2016)
The classic discussion in Brazil about the transformation industry’s function in the economic develop- ment is far from being resolved. The purpose of this article is presenting the progress of the discussion regarding whether the industry is central or not in the Brazilian economic development. The review and interpretation of literature are the research approach. As main result, it is found that there are two main groups of authors defending clearly different and delimited positions. The heterodox group continues to defend the industry centrality within the Brazilian development and the liberal group believes that there is nothing special in the industry regarding the long-term growth. Additionally to these two large groups of authors, there is a new position that relativises the industry’s central role within the Brazilian economic development.